Solving Congestion in the Plastic Surgery Match: A Game Theory Analysis. Issue 2 (February 2019) - Molina Burbano, Felipe; Yao, Amy; Burish, Nikki; Ingargiola, Michael; Freeman, Matthew; Stock, Jeffrey; Taub, Peter J.
Abstract : Summary: Plastic and reconstructive surgery is among the most competitive specialties in the residency match. Applicants seeking to maximize their chances of a successful match often submit numerous applications to the National Residency Matching Program. It is not uncommon for those applying to plastic and reconstructive surgery to apply to every program. The high application volume imparts significant time and financial burden for applicants and programs alike. Furthermore, it makes distinguishing between applicants with a genuine interest in a specific program and those who are merely hoping to improve their chances vastly more difficult. The authors sought to characterize trends in the match rate, as the number of integrated plastic and reconstructive surgery programs continues to increase. Furthermore, they reviewed the literature on game theory for possible solutions to residency application congestion. The authors propose the use of the game theory model to explain the observed results and show why an application limit is the most reasonable approach to address this issue. Abstract : This and Related "Classic" Articles Appear on Prsjournal.com for Journal Club Discussions.